Investigation of nanoparticles on cell elasticity using the nanoindentation method - Pak, Burak Aslancan; Kelleci, Kubra; Ozer, Sevil (TAYLOR & FRANCIS INC, 2024)
Nowadays, the biomechanics of living cells has been the focus of attention, as high-resolution techniques such as atomic force microscopy (AFM) allow the properties of living cells to be studied with nanoscale and precision. There are a lot of results showing that the mechanical changes in the cell or its extracellular matrix (ECM) are used as a biomarker of pathological changes. Therefore, cell stiffness is an index that evaluates the status of cell cultures. Elastic properties of cells can be deduced by nanoindentation experiments with AFM. The quantitative parameter that determines cellular deformation in the nanoindentation experiment is Young's modulus. In recent studies, it has also been shown that gold nanostructures (Au-NP) can play an active role in the detection-diagnosis of diseases and/or targeting tumor and inflammatory cells for therapeutic reasons. In this study, first of all, 2D axial biomechanical models of keratinocytes and glioma cells were made with the Finite Element Method (FEM modeling) and their mechanical properties were calculated. The deformation and mechanical changes that occur in the cell during the uptake and distribution of gold nanostructures were also investigated through the modeling. Keratinocyte cells modeled in the study are epidermal cells that make keratin, and Glioma is a group of tumor cells formed in glial cell cells, which are the supporting tissue of the brain. The Young Modulus values calculated using the Hertz model and elasticity values obtained from different techniques in the literature were compared with the simulation outputs.
Keywords: Nanoindentation; gold nanoparticles; AuNP-cell interaction; mechanical detection of deformed cells; cell elasticity value; young modulus; atomic force microscopy; force spectroscopy; MAGNETIC NANOPARTICLES; SIZE; Mechanics